Method to create and optimize original electric power communication network based on K-means - Xin JIN; Liang YANG; Cheng-ming JIN; Guo-hua SU; Lei SUN (Tongxin xuebao)
The major contribution was using the K-means to create nodes instead of traditional Waxman means in order to get a suitable and strong original electric power communication network.After the nodes were created,a vulnerability analysis was given on the grid of the network topology and check that if it has a network islanding,at last the weak nodes would be reinforced.A simulation about this algorithm shows that this algorithm which combines K-means and vulner-ability can create a electric power communication networks with better resistance of risks.